Time trends in colorectal cancer incidence across the BRICS: an age-period-cohort analysis for the GBD 2021 - Zhang, Chengcheng; Chen, Linzhi; Zhang, Chun; Xiu, Yuqi; Zhang, Hongling; Ying, Wenjuan; Liu, Hui (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) is a leading global health burden, contributing significantly to disability-adjusted life years and economic burden. The BRICS nations—spanning diverse and rapidly evolving socio-economic contexts—are undergoing critical epidemiological transitions. Understanding CRC trends in these countries is essential to inform targeted control strategies.MethodsData from the Global Burden of Disease (GBD) 2021 database were used to assess trends in CRC incidence across BRICS countries from 1990 to 2021. An age-period-cohort (APC) model with the intrinsic estimator (IE) algorithm was employed to disentangle the independent effects of age, period, and cohort on incidence rates. Data were stratified into 5-year age groups, and 95% uncertainty intervals (UIs) were calculated to reflect variability and estimation precision.ResultsFrom 1990 to 2021, the global CRC cases increased by 139.38%, with the age-standardized incidence rate (ASIR) rising by 6.52%. Among BRICS nations, Saudi Arabia had the largest increase in cases (111.02%), while United Arab Emirates showed a decline (-23.04%). Globally, most age groups exhibited positive local drift values, indicating rising incidence rates, except for individuals under 20 years. This pattern was also observed in India and South Africa, whereas Ethiopia showed a distinct trend. Brazil, China, Egypt, Iran, and Saudi Arabia experienced consistent increases across nearly all age groups. The age effect revealed a low CRC risk before age 35–39, with risk rising steadily and peaking at age 90–94, a pattern consistent across all countries. Period effects were relatively stable globally, with increasing trends in all BRICS nations except Ethiopia. Cohort effects generally increased over time, stabilizing in recent birth cohorts, with a steeper rise among males. However, India and Ethiopia showed declining cohort risks.ConclusionThis study highlights a substantial global increase in CRC incidence, with notable variations across BRICS nations over the past three decades. The observed age, period, and cohort effects underscore the need for age-specific and gender-sensitive health policies. Ongoing surveillance, research, and targeted public health interventions are critical to mitigating the rising CRC burden and improving health outcomes in these rapidly evolving regions.